2017
DOI: 10.1093/mnras/stx3096
|View full text |Cite
|
Sign up to set email alerts
|

Modelling dust polarization observations of molecular clouds through MHD simulations

Abstract: The BLASTPol observations of Vela C have provided the most detailed characterization of the polarization fraction p and dispersion in polarization angles S for a molecular cloud. We compare the observed distributions of p and S with those obtained in synthetic observations of simulations of molecular clouds, assuming homogeneous grain alignment. We find that the orientation of the mean magnetic field relative to the observer has a significant effect on the p and S distributions. These distributions for Vela C … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(86 citation statements)
references
References 71 publications
(110 reference statements)
5
81
0
Order By: Relevance
“…However, an observer with an edge-on view of the shock, would perceive a strong component along the line-of-sight. In fact, the synthetic polarization vectors of the edge-on view of the King et al (2018) super-Alfvenic colliding flow model looks very similar to our F2 observations. Chen et al (2017) examined the impact of velocity perturbations in colliding flow simulations on the resulting field morphology.…”
Section: Orientation Of F2 In Comparison To the Magnetic Field In Omc1supporting
confidence: 82%
See 1 more Smart Citation
“…However, an observer with an edge-on view of the shock, would perceive a strong component along the line-of-sight. In fact, the synthetic polarization vectors of the edge-on view of the King et al (2018) super-Alfvenic colliding flow model looks very similar to our F2 observations. Chen et al (2017) examined the impact of velocity perturbations in colliding flow simulations on the resulting field morphology.…”
Section: Orientation Of F2 In Comparison To the Magnetic Field In Omc1supporting
confidence: 82%
“…To date, a variety of simulations have explored the properties of magnetized filaments, and it is clear that the nature of the alignment between filaments and magnetic fields is inseparable from the role magnetic fields play in the formation of filaments (e.g., Seifried & Walch 2015). For example, if the gas is weakly magnetized and filaments are produced by shocks, the magnetic field may be disordered, which in turn reduces the effective polarization and impacts the apparent direction of the field (Hull et al 2017;King et al 2018;Seifried et al 2019). If the magnetic field is weak in F2, the relative orientation of F2 and the dust polarization we find might not indicate the real orientation of the magnetic field.…”
Section: Orientation Of F2 In Comparison To the Magnetic Field In Omc1mentioning
confidence: 99%
“…1. Geometry of the Athena simulations with notation conventions for the Cartesian coordinates annotated, reproduced from King et al (2018). Converging flows produce a sheet-like post-shock region, in which the initially oblique magnetic field is compressed and bent.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Quantitatively, column density and polarization fraction have significant anticorrelation in log-space (Poidevin et al 2013;Planck Collaboration Int. XIX 2015;Fissel et al 2016;King et al 2018), which suggests a power-law type dependence of decreasing polarization fraction with increasing column density, though this relationship is subject to significant scatter. Morphologically, their joint correlations have not strongly suggested a more complex relationship, being often found to be joint lognormal, though it is possible that higher resolution observations could reveal higher order structure in the future.…”
Section: Power-law Depolarization Modelsmentioning
confidence: 99%
“…Dust grains align themselves perpendicular to the local magnetic field lines (Lazarian & Hoang 2007), and the resultant polarised thermal emission can then be observed as a tracer of the field structure (Planck Collaboration et al 2016). Observations of dust polarisation in GMCs have recently revealed turbulent magnetic field structures in star forming cores (Girart et al 2013;Ching et al 2017;Hull et al 2017;King et al 2018), as well as cores threaded with distinctly uniform fields (Chapman et al 2013;Pattle et al 2017). Although the intricacies of the dust alignment mechanism make extracting the exact magnetic field morphology from polarisation maps difficult (King et al 2018), the technique has demonstrated that magnetic fields in star forming cores and throughout the universe are complex structures that vary from uniform and ordered to tangled and chaotic (Cox et al 2018).…”
Section: Introductionmentioning
confidence: 99%